GAMBARAN PENGELOLAAN LINEN DI BAGIAN LAUNDRY RSPAU Dr. SUHARDI HARDJOLUKITO YOGYAKARTA - Mentari Mungesti; Novita Sekarwati; Eva Runi Khristiani (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2016)
ABSTRACTHospital has hazards potential very risky, one of them in laundry department. The laundry department has potential hazards such as physical, chemical, biological, ergonomic and psychosocial derived  from linen of treatmentsprocess, laundry physical part and the non-compliance employeesin  wearing personal protective equipment which will cause nosocomial infection. The purpose of this research is to knowlinen management description in the laundry department RSPAU Dr. Suhardi Hardjolukito Yogyakarta. This type of research is a survey research with cross sectional approach and analyzed descriptively. The populations in this research all linen management personnel at the laundry department in RSPAU Dr. Suhardi Hardjolukito which amounts to 9 people. This research instrument uses a check list to determine linen management, laundry physical part and the use ofpersonal protective equipment by linen management employees.Analysis results descriptively indicated that in linen of treatments there was 80% category according to standards and 20% did not meet the requirements, in laundry physical part 75% category was corresponding standards and 25% category did not ﬁ t the standards and the use of personal protective equipment was 100% categories incomplete.The conclusion from this research was linen of treatments, laundry physical part and the use of personal protective equipment in RSPAU Dr. Suhardi Hardjolukito Yogyakarta did not ﬁ t the standard according to the Decreeof Health Minister Number 1204 in 2004.